Occupants' interaction with low-carbon retrofitted homes and its impact on energy use - Topouzi, M (2016)
Current regulatory and other policy trends in housing refurbishment relating to low-carbon performance standards tend to involve complex technologies and systems as well as innovative solutions to achieve 80% emissions reduction in line with the UK national target for 2050. Indicators of domestic energy performance tend to assume ideal performance of materials, complex systems and services, and that they are installed to high standards and under specific conditions, as well as rational occupant behaviour and interactions. Previous studies exploring the influence of socio-technical factors on the UK’s domestic energy use highlight that one of the main reasons for under-performance of individual projects is the lack of understanding of how people interact with domestic technology. Considering this, and given that there is still little evidence on deep refurbishments that implement low-carbon 'whole house' approaches in the UK, this research explored occupants' interaction with heating and ventilation measures as these were designed, installed and operated. The main concern was to identify the type of interactions that occur between occupants (social housing tenants) and building systems (mainly low-carbon heating and ventilation systems), and how that influences actual energy use. Using a sample of 26 social housing properties involved in the Retrofit for the Future competition in the UK, the study employed an socio-technical mixed methods approach, in which qualitative and quantitative empirical data were explored together, cross-checking occupants' 'doings' and 'sayings'. A combination of theories was used to analyse the complex interrelated factors involved in users’ interaction with building systems. The analysis identifies key factors that affect significantly occupants’ everyday practices and their interactions with the new measures: thermal comfort and pastexperiences with measures and controls; knowledge and skills (of both occupants and those involved in the project); design of the technical interventions (systems/measures) and quality of their installation. The findings from this research showed that active measures (such as intelligent and conventional heating controls, MVHR boosters, etc.) fostered direct interaction with active users when there were no design or installation faults. On the contrary, low-carbon measures that are designed and installed to be passive (such as MVHR systems operation) tend, in practice, to involve indirect interactions with active users. The research findings provide an insight into the 'in-use' factors, demonstrating to policy makers and implementers of mass refurbishment programmes the need for a framework where critical combinations of different measures and design solutions are targeted on specific house types, locations and households, in order to achieve maximum savings. Higher standards in installation of the new measures and improved quality control are also found to be a key part of refurbishment policies.